The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/sjg.sjg_91_17
|View full text |Cite
|
Sign up to set email alerts
|

Optimized high-dose amoxicillin–proton-pump inhibitor dual therapies fail to achieve high cure rates in China

Abstract: Background\Aim:Quadruple daily administration of proton-pump inhibitor (PPI) therapy achieves potent acid inhibition, and combined with amoxicillin, with its pharmacodynamic and pharmacokinetic characteristics, may be efficient for Helicobacter pylori eradication. We compared the efficacy of two optimized high-dose dual therapies with a bismuth-containing quadruple regimen for treating H. pylori infection. Rabeprazole dosages for H. pylori eradication were also evaluated.Patients and Methods:Treatment-naive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“… 26 40 The characteristics of the included trials are shown in Table 1 . Of the 15 trials, 11 were conducted in Asia, 29 33 , 35 40 3 in Europe, 27 , 28 , 34 and 1 in North America. 26 HDDT was given three times daily in four trials, 26 , 28 , 30 , 34 and four times daily in the others.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 26 40 The characteristics of the included trials are shown in Table 1 . Of the 15 trials, 11 were conducted in Asia, 29 33 , 35 40 3 in Europe, 27 , 28 , 34 and 1 in North America. 26 HDDT was given three times daily in four trials, 26 , 28 , 30 , 34 and four times daily in the others.…”
Section: Resultsmentioning
confidence: 99%
“… 26 HDDT was given three times daily in four trials, 26 , 28 , 30 , 34 and four times daily in the others. 27 , 29 , 31 33 , 35 40 Six trials used TT, 26 , 28 31 , 36 seven used BQT, 27 , 33 35 , 37 , 38 , 40 one used non-BQT, 39 and one used both TT and ST as control regimen. 32 Nine trials recruited treatment-naive patients, 30 , 33 40 four recruited treatment-experienced patients, 27 29 , 31 one recruited both, 32 and one did not report treatment experience of included patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study[ 23 ] tested the Yang et al . hypothesis that “optimized” PPI–amoxicillin dual anti- H. pylori therapy would achieve high cure rates.…”
Section: Optimized Dual Therapymentioning
confidence: 99%